2017
DOI: 10.1111/den.12926
|View full text |Cite
|
Sign up to set email alerts
|

In vivo diagnosis of early‐stage gastric cancer found after Helicobacter pylori eradication using probe‐based confocal laser endomicroscopy

Abstract: pCLE may be helpful for the diagnosis of ambiguous ECG found after Hp eradication because it enables real-time scanning throughout the lesion and detection of subsurface microstructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The present study showed that dark pleomorphic nests and disorganized irregular‐shaped dark glands were observed in patients with rectal metastasis from lung adenocarcinoma and SEL‐like extremely well‐differentiated gastric adenocarcinoma, respectively. We also reported that probe‐based CLE showed irregular dark nests in jejunal metastasis from cervical cancer, disorganized irregular dark glands in early‐stage gastric cancer covered by nontumorous regenerative epithelium or maturated atypical glands found after Helicobacter pylori eradication, and back‐to‐back orientation of dark crypts in ulcerative colitis‐associated differentiated adenocarcinoma and dark trabecular architecture in ulcerative colitis‐associated undifferentiated adenocarcinoma . The Miami classification system based on a consensus of probe‐based CLE users to standardize categorization of images indicated that all cancers in the esophagus, stomach, colorectum, and biliary duct were characterized by disorganized structures of dark (“nonrefractile”) epithelium or cells .…”
Section: Discussionmentioning
confidence: 85%
“…The present study showed that dark pleomorphic nests and disorganized irregular‐shaped dark glands were observed in patients with rectal metastasis from lung adenocarcinoma and SEL‐like extremely well‐differentiated gastric adenocarcinoma, respectively. We also reported that probe‐based CLE showed irregular dark nests in jejunal metastasis from cervical cancer, disorganized irregular dark glands in early‐stage gastric cancer covered by nontumorous regenerative epithelium or maturated atypical glands found after Helicobacter pylori eradication, and back‐to‐back orientation of dark crypts in ulcerative colitis‐associated differentiated adenocarcinoma and dark trabecular architecture in ulcerative colitis‐associated undifferentiated adenocarcinoma . The Miami classification system based on a consensus of probe‐based CLE users to standardize categorization of images indicated that all cancers in the esophagus, stomach, colorectum, and biliary duct were characterized by disorganized structures of dark (“nonrefractile”) epithelium or cells .…”
Section: Discussionmentioning
confidence: 85%
“… 2 Even if regenerating nontumorous epithelium overlies the tumorous tissue, pCLE may be able to detect it by visualization of the subsurface microscopic architecture less than 100 μm in depth. 3 In conclusion, pCLE could help in the in vivo diagnosis of submucosal hypervascular tumors such as GIST in cases in which biopsy is not recommended.…”
mentioning
confidence: 97%
“…For the first cohort of 20 SNADET lesions (16 adenomas and 4 carcinomas), pCLE scanning of the targeted lesions and the adjacent normal mucosa was retrospectively evaluated and suggestive abnormal pCLE findings were examined in relation to their histological findings. To define suggestive pCLE findings to distinguish non-neoplastic and neoplastic tissue in SNADET lesions, we consulted several reports about pCLE findings of neoplastic tissues in the gastrointestinal tract 4 6 7 8 15 16 17 . Features capable of distinguishing gastrointestinal non-neoplastic and neoplastic tissue by pCLE imaging have been summarized in the Miami Classification system 4 .…”
Section: Methodsmentioning
confidence: 99%